Contractive-Like Mapping Principles in Ordered Metric Spaces and Application to Ordinary Differential Equations. (10th May 2010) - Caballero, J.; Harjani, J.; Sadarangani, K.
Abstract : The purpose of this paper is to present a fixed point theorem for generalized contractions in partially ordered complete metric spaces. We also present an application to first-order ordinary differential equations.